Exploring lived experiences in home-based psychiatric care: a qualitative study of service users, families, and professionals in Spain - Besoaín-Cornejo, Ana María; Gil-Girbau, Montserrat; Alouali-Moussakhkhar, Mariam; Baladón Higueras, Luisa; Sáez, Josefina; Rubio-Valera, Maria (Frontiers in Psychiatry, 2025)
IntroductionPsychiatric home care provides a wide range of multidisciplinary, user-centered, high-intensity psychiatric interventions to manage mental health crises. Previous studies have found high satisfaction with care, but only assessed user and nurse perspectives. This study aimed to understand the experience of a psychiatric home hospitalization program in Spain from the perspective of all involved (users, families and healthcare professionals).Materials and methodsA qualitative study with a phenomenological approach was conducted to assess “Crisis Resolution and Home Treatment” (CRHT), a psychiatric home care program. Semi-structured individual and group interviews were held between 2021 and 2022. The final sample size was determined by saturation and data were analyzed thematically. Analyses were performed by a multidisciplinary team and externally reviewed by a mental health user and an experienced CRHT manager.ResultsFour main themes summarizing CRHT experiences emerged: (1) Organizing and operating CRHT programs; (2) Receiving care at home; (3) Caregiver and family involvement and (4) Consequences of the home-based care model. CRHT allows individualized and contextualized treatment. Users and families valued home care and felt safe, although unprepared for the post-discharge situation, especially as care intensity decreases. While home care strengthens family bonds, some caregivers may need additional support to manage a crisis. Along with personalized care, CRHT allows for the development of a comprehensive lifelong treatment plan, although the care burden (for oneself and others) must be considered.ConclusionCRHT was rated positively as a flexible intervention, facilitating person-centered care and strengthening trust between users, their families, and the CRHT team. It offers personalized treatment and connects individuals to further support, enabling better treatment experiences and strengthening family relationships.